Pengaruh Posisi Tubuh terhadap Kualitas Teknik Umpan dalam Permainan Bola Voli - Sari, Felinda (LPPM UNIVERSITAS MUHAMMADIYAH MUARA BUNGO, 2025)
Volleyball is a team sport that requires optimal mastery of techniques and body coordination, particularly in passing or setting skills. This study aims to examine the influence of body positioning on the technical quality of passing in volleyball among university students. A quasi-experimental method with a one-group pretest-posttest design was employed, involving 35 students from the Physical Education Study Program at Universitas Aisyah Pringsewu. Participants underwent a structured body positioning training program for two weeks, with assessments conducted before and after the intervention. Data were collected through direct observation using an assessment rubric covering pass direction, ball height, as well as pass stability and speed. The results indicated significant improvements in all technical aspects, with the most substantial increase in pass stability and speed. The paired sample t-test revealed a statistically significant difference (p = 0.000 < 0.05) between pretest and posttest scores. These findings demonstrate that proper body positioning significantly enhances passing quality by improving postural control, core stability, and proprioceptive function. It is concluded that integrating biomechanically-based body positioning training into volleyball coaching programs, particularly in higher education settings, can optimize technical performance and support more effective game strategies.